Pandemic on Public Health: A Systematic Review - Betriani Disik; Lucia Yogyana Suramas; Hayuti Windha Pagiu (Medical Studies and Health Journal (SEHAT), 2024)
The COVID-19 pandemic has had a significant impact on the global public health system, with developing countries left vulnerable due to limited infrastructure and resources. This research aims to explore the effectiveness of health communication strategies in increasing public compliance with health protocols during a pandemic in developing countries. The research method used is a systematic review using the PRISMA method. The research results show that an integrated health communication strategy, including the use of mass media and social media, can increase health literacy and promote healthy behavior amidst existing infrastructure challenges. The implication of this research is the importance of developing adaptive communication strategies to support an effective public health response, with a focus on strengthening health infrastructure and supporting frontline health workers. Future research could expand understanding of the use of new technologies in health communication and deepen understanding of the psychological, social, and economic factors that influence adherence to health protocols.